Control system and structure of an unmanned aerial vehicle - Phua, Jian Ming (2017)
Technological advances have reduced the cost and increased the performance of drones such that it has become easily accessible by the public and no longer used solely for military purposes. Quadcopter is the most popular choice among users for hobby use and commercial usage. A hexacopter can achieve stable vertical flight and can be used for a magnitude of purposes such as surveying tall structures, filmography and aiding search and rescue operations. The goal of this final year project is to build a hexacopter and understand the control system and structure behind it. The hexacopter uses a Pixhawk flight controller which interfaces with the Global Positioning System (GPS), accelerometer, barometer, Electronic Speed Controller (ESC), motors, radio system and telemetry. Individual components are tested and assembled together to create the hexacopter. The flight controller can record and save flight data logs onto its on board Secure Digital (SD) card which can be accessed using an open source flight management software called Mission Planner. Using this software, the flight controller can be calibrated and configured to the hexacopter. Logs can be studied to determine the cause of problems and can be troubleshoot. Multiple outdoor test flights were conducted to understand the control behaviour of the hexacopter and its capability. The hexacopter is capable of stable flight, with GPS working and logging of flight data, also full autonomous flight is achieved during the last few testing phases. This report aims to track the study of the hexacopter, components selection, assembly and implementation of autonomous flight.